Born Outside of Wedlock, Died as a Millionaire: Getting Wealthy by Being Entrepreneurially Resourceful - Matti Koiranen; Hannele Rautamäki (Athens Journal of Business & Economics, 2024)
The rise from rags to riches i.e., from poverty to wealth has inspired as a topic both novelists and historians, but often their texts are just chronological or sub-thematic writings without any clear theoretical focus. In the present study, the learned entrepreneurial resourcefulness has been selected to be the main theoretical perspective. In addition, we can follow from a life-long description how a youngster called Julius (Julius Johnsson; 1845-1923) born in the poverty rose to wealth. The context is Finland, mainly in the 19th century, and the historian’s biographical data are used as empirical evidence. Our analytical tool is a 2x2-matrix, which makes it possible to study both individual and collective resourcefulness and both proactive and reactive behaviour in the growth process. The key findings emphasize proactive, self-initiated behaviour. Both individual and collective resourcefulness have helped the youngster in his development ”from a Russian bastard” to a Finnish millionaire. The nature of his resourcefulness has been not only cognitive but also affective and, most of all, conative. Resourcefulness has helped Julius to recognize opportunities and overcome resource constraints in the transition to a wealthy habitual entrepreneur and a respected businessman. Earlier body of knowledge regarding resourcefulness is complemented with our analytical matrix which can be regarded as the main methodological contribution and which offers a novel framework for the forthcoming studies aiming at adding knowledge on entrepreneurial resourcefulness.